Skin diseases among adults in Tasiilaq, East Greenland - Morten B. Haulrig; Anna M. Andersson; Julia-Tatjana Maul; Jingyuan Xu; Su M. Lwin; Carsten Flohr; Lone S. Hove; Tove Agner; Anders Koch; Christopher E. M. Griffiths; Claus Zachariae; Jacob P. Thyssen (International Journal of Circumpolar Health)
Cold climate and unique genetic and environmental factors may influence the prevalence of skin diseases in Greenland. However, there is a lack of epidemiological studies on skin diseases in the adult Greenlandic population. To address this unmet need a cross-sectional study, run by dermatologists from Denmark, the UK, and Switzerland estimated the prevalence and clinical manifestations of skin diseases among adults in East Greenland in May 2022. All adults ≥18 years in the town of Tasiilaq were invited, and 295 individuals aged 18–78 years participated (22.5% of the overall adult population in Tasiilaq). Two-hundred and three participants (69%) had visible signs of current skin disease, and among these, 242 cases of dermatoses were identified. The most common skin diseases were hand eczema (22.4%), lichen simplex (9.5%), discoid eczema (7.1%), psoriasis, atopic dermatitis and acne vulgaris (5.8% each). Scabies was the most frequent infectious skin disease (4.4%). No cases of skin cancer were identified. Atopic dermatitis and psoriasis presented with disease that was of limited extent and different from the classical presentations. Skin diseases showed a high prevalence among adults in East Greenland, and some of them were severe. This indicates a noteworthy public health problem that warrants better access to dermatologist support.